Pengujian Kegunaan Sistem Keuangan Desa (SISKEUDES) Menggunakan System Usability Scale (Studi Kasus :Desa di Kabupaten Purbalingga): Village Financial Management, Village Financial System (SISKEUDES) and System Usability Scale (SUS) - Bayu Wira saputra; Dwi Januarita AK; M. Eka Purbaya (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
The presence of the law on villages, namely Law No. 20 of 2018 strengthens the status of the village as a community government as well as the power of the village to build infrastructure and empower village communities. As support to the Village Government by utilizing information and communication technology in managing village finances, the Government developed an application called the Village Financial System (SISKEUDES). The SISKEUDES application is an application developed by the Financial and Development Supervisory Agency (BPKP) in order to improve village financial governance. The features in the SISKEUDES application are made simple and user friendly, making it easier for users to operate the SISKEUDES application. However, to run the SISKEUDES application, there are still obstacles, namely the availability of human resources (HR) and village officials who do not master computers. After the implementation of the application in the village government, in fact in the use of SISKEUDES there is still a mismatch in the use of an information system with what is expected by the user of the application. This study required testing of 69 villages in Purbalingga Regency, with one village and one respondent, namely village officials who used the SISKEUDES application. The system usability testing model that is known to be able to perform this task is to use the System Usability Scale (SUS) questionnaire framework to measure usability aspects according to the user's subjective assessment. The purpose of this study was to measure the usefulness of SISKEUDES using the System Usability Scale with a Village Case Study in Purbalingga Regency. In this study, to obtain data, a System Usability Scale (SUS) questionnaire was made for village officials using SISKEUDES with a total sample of 69 respondents. The results showed that the majority of village officials were satisfied (Above Average) with SISKEUDES (Village Financial System) which was 59 village officials (86%) while the remaining 10 village officials (14%) were dissatisfied (Below Average) with SISKEUDES (System Village Finance).